Undoing gender with institutions: Lessons from the German division and reunification - Quentin Lippmann; Alexandre Georgieff; Claudia Senik-Leygonie (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Using the 41-year division of Germany as a natural experiment, we show that the GDR's gender-equal institutions created a culture that has undone the male breadwinner norm and its consequences. Since reunification, East Germany still differs from West Germany not only by a higher female contribution to household income, but also because East German women can earn more than their husbands without having to increase their number of housework hours, put their marriage at risk or withdraw from the labor market. By contrast, the norm of higher male income, and its consequences, are still prevalent in West Germany.
Keywords: D13; I31; J16; P51; Z1; 330; Gender norms; Culture; Institutions; German division; Family; Housework; Divorce; Labor market